Pliego suelto fechado en 1781 - Torres Pérez, José María (Revista General de Información y Documentación, 2009)
This article focuses in an unknown printed image of two female siamese twins, born inValencia (Spain) in August 28th, 1781. The so called “monster” is presented as a break of the natural order, but the text enphasizes it is a human being above all. In representing this kind of human beings never lacked a compassive respect. The siemese twins are described and shown as a phenomenon, but also with the aim of enlightening a society whose knowledge is very limited. The article also pays attention to other images with a similar theme and approach, made in the 17th and 18th centuries.
Keywords: Unknown printed by a single face; Relation of events; Malformations